Cost-effectiveness Analysis of Feeding Guidelines for Infants Following Intestinal Surgery. Issue 5 (May 2020) - Shores, Darla R.; Mogul, Douglas; Allen, Julia; Delarmente, Benjo A.; Padula, William
ABSTRACT: Objective: The aim of the study was to determine the cost-effectiveness of postoperative feeding guidelines to reduce complications in infants with intestinal surgery compared to standard feeding practices. Methods: Using outcomes from a cohort study, Markov models from health care and societal perspectives simulated costs per hospitalization among infants fed via guidelines versus standard practice. Short-term outcomes included intestinal failure–associated liver disease, necrotizing enterocolitis after feeding, sepsis, and mortality. Effectiveness was measured as length of stay. The incremental cost-effectiveness ratios (ICER) compared cost over length of stay. Univariate and multivariate probabilistic sensitivity analyses with 10, 000 Monte Carlo Simulations were performed. A second decision tree model captured the cost per quality-adjusted life years (QALYs) using utilities associated with long-term outcomes (liver cirrhosis and transplantation). Results: In the hospital perspective, standard feeding had a cost of 31, 258, 902 and 8296 hospital days, and the feeding guidelines had a cost of 29, 295, 553 and 8096 hospital days. The ICER was −9832 per hospital stay with guideline use. More than 90% of the ICERs were in the dominant quadrant. Results were similar for the societal perspective. Long-term costs and utilities in the guideline group were 2830 and 0.91, respectively, versus 4030 and 0.90, resulting in an ICER of −91, 756/QALY. Conclusion: In our models, feeding guideline use resulted in cost savings and reduction in hospital stay in the short-term and cost savings and an increase in QALYs in the long-term. Using a systematic approach to feed surgical infants appears to reduce costly complications, but further data from a larger cohort are needed. Abstract : Supplemental Digital Content is available in the text